EVALUASI PENCATATAN DAN PELAPORAN ASET TETAP PEMERINTAH DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA KENDARI - Mayasani, Dewi Nur (JURNAL AKUNTANSI, 2016)
This study aims to determine the consistency of Fixed Asset Recording and Reporting on Local Government Finance and Asset Management Agency Regions (BPKAD) Kendari City under PP No. 24 of 2005.        The method used is descriptive analysis. Processing and analysis of qualitative data is done interactively which consists of four steps, namely: 1) collection of data, 2) data reduction, 3) Presentation of data, 4) Withdrawal conclusion / verification.              The results showed that the activity of recording and reporting of fixed assets is carried out by the Finance and Asset Management Agency Regional Kendari accounting period in 2010-2012 is not in accordance with Regulation PP No. 24 of 2005 on the Government Accounting Standards. This is because the presence of a discrepancy between the records maintained by the presentation contained in the financial statements, in addition to that there is an error in the classification and disclosure activities and the non-realization of fixed assets depreciation on fixed assets and no presentation of Notes to the Financial Statements as on education.Keywords: Recording, Reporting, Fixed Assets